1999
DOI: 10.1027//0227-5910.20.2.59
|View full text |Cite
|
Sign up to set email alerts
|

Domestic Integration and Suicide in the Provinces of Canada

Abstract: Canada's rate of suicide varies from province to province. The classical theory of suicide, which attempts to explain the social suicide rate, stems from Durkheim, who argued that low levels of social integration and regulation are associated with high rates of suicide. The present study explored whether social factors (divorce, marriage, and birth rates) do in fact predict suicide rates over time for each province (period studied: 1950-1990). The results showed a positive association between divorce rates and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
11
0

Year Published

2008
2008
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(11 citation statements)
references
References 14 publications
0
11
0
Order By: Relevance
“…The results of our study support Durkheim's theory, as well as some newer studies (Johnson, 1965) that consider a higher level of social and family integration to be protective. Whereas Durkheim suggested that both extremely high and extremely low levels of social integration and social regulation are associated with high suicide rates, Johnson (1965) argues that in modern societies only low levels of these social characteristics are associated with high suicide rates (Leenaars and Lester, 1999). According to Durkheim, traditional family life provides the best protection against selfdestructive behavior.…”
Section: Discussionmentioning
confidence: 99%
“…The results of our study support Durkheim's theory, as well as some newer studies (Johnson, 1965) that consider a higher level of social and family integration to be protective. Whereas Durkheim suggested that both extremely high and extremely low levels of social integration and social regulation are associated with high suicide rates, Johnson (1965) argues that in modern societies only low levels of these social characteristics are associated with high suicide rates (Leenaars and Lester, 1999). According to Durkheim, traditional family life provides the best protection against selfdestructive behavior.…”
Section: Discussionmentioning
confidence: 99%
“…To capture social disintegration, the divorce rate was used as the third main independent variable. The divorce rate has been found in sociological science as the strongest and most reliable indicator of social disintegration (Ben Park & Lester, 2006;Breault, 1986;Fernquist, 2007;Leenaars & Lester, 1999;Stack, 2000). It was measured as the percentage of women divorced, 1990.…”
Section: Variables and Measurementmentioning
confidence: 99%
“…Past reports have shown that measures of area social disintegration, such as divorce rates are consistently strong predictors of suicide (Breault, 1986;Evans et al, 2004;Fernquist, 2007;Leenaars & Lester, 1999;Neumayer, 2003;Trovato, 1986). Other studies have found that area social disintegration measures are stronger determinants of suicide than area deprivation and area socioeconomic status (Crawford & Prince, 1999;Middleton, Whitley, Frankel, & Dorling, 2004;Whitley, Gunnell, Dorling, & Davey-Smith, 1999).…”
Section: Introductionmentioning
confidence: 98%
“…Durkheim postulated a negative correlation between societal suicide rates and social integration (defined as the extent to which members of society are bound together in social relationships). Birth rates (Lester & Yang, 1992;Leenaars, Yang, & Lester, 1993;Lester, 1994aLester, , 1994bLester, , 1994cLester, , 1996Lester, , 1999Wiedenmann & Weyerer, 1994;Lester & Garcia, 1995;Leenaars & Lester, 1999;Bridges & Pearson, 20041, fertility rates (Austin, Bologna, & Dodge, 1992), marriage rates (Leenaars, et al, 1993;Lester, 1994aLester, , 199413, 1994cLester, , 1996Lester, , 1999Wiedenmann & Weyerer, 1994;Lester & Garcia, 1995;Leenaars & Lester, 1999), divorce rates (Austin, et al, 1992;Lester & Yang, 1992;Leenaars, et al, 1993;Lester, 1999;Leenaars & Lester, 1999), and unemployment rates (Austin, et al, 1992;Lester & Yang, 1992;Leenaars, et a/., 1993) have been used as proxies for the amount of societal integration in studies of suicide rates. Additionally, presence of spouse and children is thought to improve social integration and reduce suicide rates (Durkheim, 1992).…”
mentioning
confidence: 99%